The Implementation of Reading Indicators of Syllabus and Questions Reading in Smart Steps 2 Textbook - Tri Winindyasari Palupi; Yulieda Hermaniar (Lentera: Jurnal Ilmiah Kependidikan, 2020)
English textbooks must be suitable and refer to the syllabus, especially among the questions in the textbook and the indicators of the syllabus that have been defined. Both of them are related to each other, which in each indicator of the syllabus will be implemented in a textbook. The research objective is to know the implementation of reading indicators of syllabus and questions reading in the Smart Steps 2 textbook. This research is the documentation method, with the subject is all the reading texts in the English Smart Steps 2 textbook. While the object of this research is all of the questions of the reading texts which have been analyzed and are found in the English Smart Steps 2 textbook. Based on the data analysis, it is found that there are 17 reading texts and questions based on the text in the textbook Smart Steps 2. And it is found two reading skills (reading comprehension and scanning) which every questions reading have based on that text in the Smart Steps 2 textbook. According to the result, it can be concluded that questions reading in the textbook Smart Steps 2 is implemented with all reading indicators of the syllabus.